1999
DOI: 10.1037/0012-1649.35.4.1143
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in time estimation: Comparing childhood and old age.

Abstract: Participants from ages 5 to 99 years completed 2 time estimation tasks: a temporal generalization task and a temporal bisection task. Developmental differences in overall levels of performance were found at both ends of the life span and were more marked on the generalization task than the bisection task. Older adults and children performed at lower levels than young adults, but there were also qualitative differences in the patterns of errors made by the older adults and the children. To capture these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
168
4
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(207 citation statements)
references
References 28 publications
33
168
4
2
Order By: Relevance
“…If there are age differences on pitch identification, it would suggest that there may be a general age-related decline in absolute identification performance, rather than a specific impairment in temporal processing in older adults. We note that such a finding has consequences for the interpretation of the findings from previous recent studies, including our own, that have established age-related declines in judging duration (McCormack et al, 1999;.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…If there are age differences on pitch identification, it would suggest that there may be a general age-related decline in absolute identification performance, rather than a specific impairment in temporal processing in older adults. We note that such a finding has consequences for the interpretation of the findings from previous recent studies, including our own, that have established age-related declines in judging duration (McCormack et al, 1999;.…”
Section: Methodsmentioning
confidence: 58%
“…First, there could be an increase with age in the variability or noise associated with internal clock, memory processes, or both (McCormack et al, 1999;). An increase in noise with age would lead to a general reduction in overall levels of performance.…”
mentioning
confidence: 99%
“…A version of the generalization task was used that had been designed for participants who may find it difficult to understand abstract computerized tasks (such as children or very elderly adults ; McCormack et al 1999). Rather than instructing participants to identify a standard, the stimulus identification task was set in an easily comprehensible context.…”
Section: Methodsmentioning
confidence: 99%
“…However, the extent to which gradients are asymmetrical in this way in any given study also reflects the veridicality of longterm memory of the standard. Previous research suggests that the representation of the time intervals may become distorted in long-term memory Shurtleff et al 1992), with the standard being systematically mis-remembered as being either shorter (McCormack et al 1999) or longer (Wearden et al 1999 ;McCormack et al 2002) than it actually was. Since responses are made by comparing the memory representation of the standard with the representation of the current test stimulus, such distortion will affect the probability that erroneous positive responses are given to stimuli shorter or longer than the standard.…”
Section: Experiments 1 : Temporal Generalizationmentioning
confidence: 99%
“…Additionally, research on aging has shown that the elderly do not show biases relative to younger individuals in their performance on the bisection task, even if the elderly are more variable in their responses (McCormack, Brown, & Maylor, 1999;Wearden, Wearden, & Rabbitt, 1997).…”
Section: Accepted Manuscript Embodying Effects 13mentioning
confidence: 99%